(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article delves into the intricate changes vowels undergo in the context of connected speech. It explores two key modifications: vowel reduction and elision. The discussion encompasses how these alterations occur in natural conversation, impacting pronunciation for efficiency and clarity. The annotation highlights the influence of surrounding sounds and regional variations on vowel modifications. It also emphasizes the significance of understanding these shifts for improved language comprehension, particularly for non-native speakers. Overall, the article illuminates the dynamic nature of spoken language and its nuanced variations, offering valuable insights into the subtleties of communication